La política española hacia el Magreb y Oriente Medio. "Primavera árabe" - Reyes, Román (Nómadas. Critical Journal of Social and Juridical Science, 2015)
To Spain is accused of having changed sides. What does not hold. Spain messages are clear and unambiguous. Something that can be seen in the records that have forced these messages. At both literature and behaviors. EU proposals for dialogue match the values that Spain has defended. His theoretical - ideological position has always been consistent. Coincident with the Euro-Arab community, regional cooperation and integration.